Expression of the matrix metalloproteinase 9 in Hodgkin's disease is independent of EBV status. Issue 3 (1st June 2000) - Flavell, J R; Baumforth, K R N; Williams, D M; Lukesova, M; Madarova, J; Noskova, V; Prochazkova, J; Lowe, D; Kolar, Z; Murray, P G; Nelson, P N
Abstract : Background —In vitro the Epstein-Barr virus (EBV) encoded latent membrane protein 1 (LMP-1) has been shown to upregulate expression of matrix metalloproteinase 9 (MMP-9), a member of a family of zinc dependent endopeptidases that is believed to facilitate tumour invasion and metastasis by degradation of the extracellular matrix. Aim —To test whether the expression of MMP-9 in Hodgkin's disease correlates with EBV status and survival and to investigate whether LMP-1 expression affects MMP-9 concentrations in the Hodgkin's disease cell line, L428. Methods —MMP-9 expression was measured by means of immunohistochemistry in a series of Hodgkin's disease tumours and this expression was correlated with EBV status and survival. The influence of LMP-1 on MMP-9 expression was also investigated in the Hodgkin's disease cell line, L428. Results —MMP-9 expression was demonstrated in the malignant Hodgkin and Reed-Sternberg cells of all (n = 86) formalin fixed, paraffin wax embedded Hodgkin's disease tumours examined. Although the intensity of MMP-9 immunostaining varied between cases, there was no correlation between MMP-9 expression and EBV status or survival. MMP-9 expression was also detected in a variety of non-malignant cells, including fibroblasts. MMP-9 was detected by zymography in the L428 and KMH2 Hodgkin's disease cell lines, whereas low or undetectable amounts of MMP-9 were found in the L591 Hodgkin's disease cell line. Induction of LMP-1 expression in the Hodgkin's disease cell line L428 did not result in a detectable increase in the values of MMP-9 as measured by zymography. Conclusions —These results demonstrate that MMP-9 is consistently expressed by the Hodgkin and Reed-Sternberg cells of Hodgkin's disease tumours and by the Hodgkin's disease cell lines, L428 and KMH2. However, this expression does not appear to be related either to LMP-1 values or to survival.